Relationship between the shape of the tibial plateau and femorotibial contact mechanics after meniscectomy in the canine stifle - Pozzi, Antonio; Natsios, Pavlos; Kim, Stanley E.; Choate, Christina J.; Conrad, Bryan P. (Frontiers in Veterinary Science, 2025)
ObjectivesThe purpose of this study was to describe the tibial plateau surface geometry and the contact mechanics after medial and lateral partial and total meniscectomies in the canine stifle.Study designThis was an ex vivo experimental study. Contact area, average contact pressure, and peak contact pressure (PCP) were recorded using a digital pressure sensor. The articular surfaces of each stifle’s tibia and femur were digitally mapped using a three-dimensional laser scanner.ResultsBased on the normalized data, lateral total meniscectomy caused significantly greater changes in PCP than medial total meniscectomy. In contrast, partial meniscectomy, whether medial or lateral, did not result in any significant differences in PCP. With a total meniscectomy, mean PCP increased by 72 and 273% for the medial and lateral meniscus, respectively. Based on the absolute values, the PCP after lateral partial meniscectomy was significantly higher than after medial partial meniscectomy. The radius of curvature of the lateral tibial plateau (12.8 ± 10.9 mm) was smaller than the radius of the medial tibial plateau (25.9 ± 17.8 mm) (p < 0.05).ConclusionBased on our results, the geometry of the medial and lateral tibial plateau may explain the different contact mechanics following medial and lateral meniscectomy. A total lateral meniscectomy may have greater detrimental effects when compared to medial meniscectomy.